SELECTIVE ALKYLATION OF ANILINE WITH METHANOL OVER METALLOSILICATES - PARK, YK; PARK, KY; WOO, SI (BALTZER SCI PUBL BV, 1994)
The selective alkylation of aniline with methanol was investigated over various metallosilicates synthesized in two different media: alkaline medium (NaOH) and fluorine medium (NH4F). Through the elemental analysis, XRD, and Si-29 MAS NMR, it was thought that all the metallosilicates had MFI zeolite structure and the metals were incorporated in metallosilicate framework successfully. Temperature programmed desorption (TPD) Of NH3 and aniline alkylation suggested that the selectivity for N,N-dimethylaniline (NNDMA) is high when the metallosilicates have a large number of medium acid sites (567-673 K), which means that the medium acid sites play an important role in the production of NNDMA. It was also known that metallosilicates synthesized in fluorine medium have strong acid sites (>773 K)and were deactivated more rapidly than those synthesized in alkaline medium.
Keywords: ZSM-5